1445. Deciphering the Role of the Y221H Ω-loop Substitution in Pseudomonas-derived Cephalosporinase (PDC) in Cephalosporin Resistance. (31st December 2020) - Mack, Andrew R; Barnes, Melissa D; Taracila, Magdalena A; Mojica, Maria F; Kumar, Vijay; Rutter, Joseph; van den Akker, Focco; Page, Malcolm; Haider, Shozeb; Bonomo, Robert A
Abstract: Background: Antimicrobial resistance is a major global health threat. Pseudomonas aeruginosa is a leading cause of nosocomial infections and a key opportunistic pathogen in cystic fibrosis. Multidrug resistant strains are classified as a "serious threat" by the CDC. Pseudomonas -derived cephalosporinase (PDC) is largely responsible for β-lactam antibiotic resistance in P. aeruginosa. Single amino acid substitutions in the essential Ω-loop region (e.g. Y221H by structural alignment-based numbering of class C β-lactamases) have been shown to enhance hydrolysis of ceftazidime (CAZ) and ceftolozane (TOL), limiting therapeutic options for P. aeruginosa . Methods: We undertook detailed studies to explore the mechanisms by which Y221H enhances CAZ and TOL MICs. MIC measurements were performed per CLSI guidelines using MH Agar. Thermal stability was determined by circular dichroism. Enzyme kinetic properties were determined using spectrophotometric techniques. Molecular dynamics techniques were used to predict structural changes. Results: E. coli expressing bla PDC-3 -Y221H is less susceptible to CAZ (MIC 0.5 mg/L WT → 8 mg/L Y221H) and TOL (MIC 2 mg/L WT → 16 mg/L Y221H). Using steady-state kinetic analysis, Y221H was found to hydrolyze CAZ with a K M = 585 µM, a k cat = 3.4 sec -1, and k cat /K M = 0.0058 µM -1 s -1. With cephalothin, a good PDC substrate, we observed K M = 26.6 µM, k cat = 70.1 s -1, and k cat /K M = 2.6 µM-1 s -1 for Y221H. Using Electrospray ionization mass spectrometry (ESI-MS), CAZ was detected covalently bound to WT, but not Y221H when incubated at 1000-fold molar excess. Avibactam (AVI) inhibited Y223H ( K i = 70 nM vs. 19 nM for WT). Y221H thermal stability decreased by 5°C (Tm = 47°C vs 52°C WT). AVI at 10-fold molar excess does not increase Tm in Y221H or WT. WT-MetaDynamics (WT MDS) predicts the opening of a hidden pocket by repositioning residue 221 (Figure 1 ).). Figure 1: (Left) We carried out enhanced sampling metadynamics simulations to generate free-energy landscapes as a function of the dihedral angles of residue 221. This identifies the differences in the dynamics of the tyrosyl side chains in the wild type Y221 and the imidazole ring of the H221 variant. (Right) The rotation of the side chain in H221 opens a cryptic pocket (green mesh), which is occluded in the wild type. The Ω-loop is colored red. Conclusion: PDC-3 Y221H increases CAZ & TOL MICs and alters catalytic activity, primarily by a change in k cat . Our modelling analyses suggest altered conformational flexibility and structure-function relationships in the Ω-loop. These results help to advance our understanding of PDC and will inform development of novel antibiotics and inhibitors. Disclosures: Robert A. Bonomo, MD, Entasis, Merck, Venatorx (Research Grant or Support)